Physical Security Assessments using Worst-Case Coverage in Wireless Sensor Networks (Journal of Nuclear Technology in Applied Science, 2025)
Most of the nuclear and radiological facilities have physical security systems  which include different types of intrusion detection cluster sensors. They should  be kept active, valid and updated and follow the requirements of the nuclear regu latory authority at the national level and meet the recommendations of IAEA at  the international level. Wireless sensor networks are crucial to many applications.  Nuclear facilities security systems are one of the major uses for wireless sensor  networks. The majority of studies conducted on wireless sensor networks con centrate on improving target coverage to save energy consumption and network  costs. One of the most important issues to take into account, when researching  the coverage problem of sensor networks is the problem of planar target analysis.  This study presents a new coordinate-free sensor network coverage model for the  plane target issue, based on Clifford algebra which is a strong tool. Additionally,  the Clifford Algebra computations of the node coverage rate for the plane target  in the sensor network are illustrated. After that, the sensor network’s worst-case  coverage (maximum clearance path) for a plane target is provided which is used  to provide security for nuclear facilities to prevent and find any intruders from  making any troubles. Through simulation, the suggested algorithm’s dependability and optimality have been demonstrated. Furthermore, a comparison is given  between the point target’s and the plane target’s breach weight. In this work, a  hypothetical nuclear site was assumed for both security system analysis and sys tem effectiveness evaluation. The systematic analysis of vulnerability to intrusion  (SAVI) program was used for evaluation process. SAVI determines the 10 vulner able paths as a measure of system effectiveness. A SAVI output result shows that  the effectiveness of the security system, PE, along the worst vulnerability path  was 82%. The System probability of detection PD was 94% of nuclear facility. This  analysis concludes that the security system of HNRC facility is winning against  the worst path of the terrorists attack and achieved its objective.
Keywords: Clifford algebra; Wireless sensor network; Worst coverage; Plane target; Physical security assess-ments; Risk model; SAVI model